2011
DOI: 10.6115/khea.2011.49.5.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Marital Satisfaction between Immigrant Wives and Korean Wives of Korean Men

Abstract: The purpose of this study was to explore factors related to marital satisfaction among immigrant wives compared to Korean wives of Korean men. Participants included 409 immigrant wives married to Korean men and 474 Korean wives married to Korean men, both currently living in Korea. Hierarchical regression analyses revealed that there were different sets of variables that predicted marital satisfaction for each group. Egalitarian decision-making was a significant predictor of marital satisfaction for immigrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Research on migrant wives has mainly focused on negative aspects such as marital conflict (O. Kim, ) and depression (Lim, ). In the early phase of acculturation, migrant wives are more likely to face adjustment difficulties because of their language barriers, culture shock, disconnection with their previous social networks, lack of information, unfamiliarity with Korean culture, and discrimination from Koreans (G. H. Chung & Lim, ; Y.‐H. Kim & Anh, ).…”
Section: An Ecological Perspective On Migrant Wives' Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on migrant wives has mainly focused on negative aspects such as marital conflict (O. Kim, ) and depression (Lim, ). In the early phase of acculturation, migrant wives are more likely to face adjustment difficulties because of their language barriers, culture shock, disconnection with their previous social networks, lack of information, unfamiliarity with Korean culture, and discrimination from Koreans (G. H. Chung & Lim, ; Y.‐H. Kim & Anh, ).…”
Section: An Ecological Perspective On Migrant Wives' Life Satisfactionmentioning
confidence: 99%
“…For example, migrant wives tend to have positive experiences despite their adjustment difficulties when they have good relationships with their husbands, receive appropriate support, and develop positive coping skills (Yoo, Hong, & Kim, ). Research has also shown that, in general, migrant wives have the following characteristics: They are optimistic about their future in Korea, their depression level is low (G. H. Chung & Lim, ; Lee & Kim, ; Lim, ), their self‐esteem or life satisfaction is relatively high (Kye, Kang, & Jeong, ; Lee & Kim, ), their marital conflict is relatively low, and their marital satisfaction is not particularly low (Seol, Lee, & Cho, ).…”
Section: An Ecological Perspective On Migrant Wives' Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…No differences in marital satisfaction were found in a national sample of African Americans and Black Caribbean immigrants, but follow‐up analyses showed higher marital satisfaction in Black Caribbean immigrant women than African American women (no differences among men; Bryant, Taylor, Lincoln, Chatters, & Jackson, ). A study of native‐born Korean wives and immigrant wives married to Korean men found no differences in marital satisfaction between these groups (Chung & Lim, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study provides critical insight into the strength and vulnerabilities of immigrant couple intimate ties by comparing trajectories of immigrant and native‐born couples' relationship satisfaction, conflict frequency, and self‐disclosure. We focus on these constructs because prior work has shown that they are distinct relationship processes commonly examined in relationship science (see Karney & Bradbury, ) that have been used in prior research comparing native‐born and immigrant couples (Bryant et al, ; Chung & Lim, ; Rehman & Holtzworth‐Munroe, , ). A second important aim of our work is to examine covariates that might account for variation in immigrant couple trajectories.…”
Section: Literature Reviewmentioning
confidence: 99%